PENGGUNAAN BERBAGAI MACAM VAKSIN PADA TERAPI KONDILOMA AKUMINATA ANOGENITAL - Wirman, Jefrizal; Anum, Qaira (Politeknik Kesehatan Kemenkes Bengkulu, 2021)
Anogenital condyloma aquiminata (AAC) is an anogenital Human papillomavirus (HPV) infection that usually manifests as papules or soft plaques on the external genitalia, perianal, perineal, or inguinal skin. In Indonesia, 13 hospitals (RS) with genital skin specialist education centers, there has been an increase in cases of condyloma acuminata in the last 5 years (2007-2011). In the Polyclinic of the Division of Sexually Transmitted Infections (STI) of the Dr. M DJamil Hospital, Padang, in 2019 there were 36 new cases and the total visits of condyloma acuminata patients who were controlled during 2019 were 288 visits. KAA therapy that is currently developing still shows a fairly high recurrence rate. Immunotherapy using vaccines has begun to be developed as an alternative therapy for AAC. The HPV vaccines, Mumps Measles Rubella (MMR), Bacillus Calmette-Guerin (BCG), and Mycobacterium indicus pranii (MIP) provide therapeutic benefit in AAC. The use of the HPV vaccine can be done intralesionally or intramuscularly. MMR and BCG vaccines are injected intralesionally. Meanwhile, the MIP vaccine was administered intradermally to both deltoids. The whole vaccine is given in several doses at different time intervals. Cellular immune stimulation is thought to be the basis for the usefulness of vaccines as therapy in AAC. There are no studies that reveal the side effects of giving vaccines as immunotherapy in AAC that are significant.